General Nursing and Family Psychoeducation Improved Anxiety and Coping Among Caregivers of Children with Intellectual Disabilities - Sophia Euodia Anggoh; Achir Yani S. Hamid; Ria Utami Panjaitan (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Innovative behavior is essential for organizations to adapt to dynamic work environments and improve employee performance. Individual psychological resources and organizational support may encourage innovation, while work attachment may function as an important mechanism in this relationship. Objective: This study aimed to examine the effectiveness of combining general nursing intervention and Family Psychoeducation (FPE) in reducing anxiety and improving coping strategies among family caregivers of children with intellectual disabilities. Methods: This study employed a quantitative approach using a survey of employees. Data were collected through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the direct and indirect relationships among psychological capital, organizational support, work attachment, and innovative behavior. Results: The results showed that both groups experienced significant reductions in anxiety after general nursing intervention; however, the intervention group demonstrated significantly greater reduction at post-test 2 compared with the control group (p